NÓKIS RAYONÍ OYKONIMLERI - Baltabayev, O.O. (SCIENCE and SOCIETY, 2024)
In this article, local geographical terms in the formation of oikonyms of the Nukus region of the Republic of Karakalpakstan, lexical-semantic features of oikonyms, the period of their occurrence are determined, some oikonyms are recommended as toponymic heritage.